Temporal dynamics of sugar beet (Beta vulgaris L.) N supply from cover crops differing in biomass quantity and composition - Koch, Heinz-Josef; Grunwald, Dennis; Essich, Lisa; Ruser, Reiner (Frontiers in Plant Science, 2022)
Cover crops are supposed to decrease the soil mineral N content during winter and increase the N delivery to subsequent main crops due to mineralization of N previously prevented from leaching. However, data on N delivery from cover crops grown before sugar beet have rarely been reported for Central European conditions. Therefore, our study aimed to provide information for cover crops differing in frost resistance and biomass quantity applicable for N fertilizer dressing in the subsequent main crop. In 2018/19 and 2019/20, field trials were conducted on two Luvisol sites in Germany typical for sugar beet cultivation, comprising a sequence of autumn sown cover crops grown after field pea followed by unfertilized sugar beet main crops sown the next spring. Apparent net N mineralization and the N delivery of cover crops on sugar beet were calculated according to a mass balance approach including Nmin and sugar beet N uptake. Winter rye and oil radish revealed the greatest potential for scavenging nitrate from the soil profile while reductions caused by frost sensitive saia oat and spring vetch were more variable. The amount of N in cover crop biomass was negatively correlated to soil mineral N in autumn and also in spring. Thus, for environmentally effective cover cropping in Central Europe, species with a sufficiently high frost tolerance should be chosen. Despite cover crop N uptake up to 170 kg N ha-1 and C:N ratios < 20, N delivery to sugar beet occurred only in March-July of the beet growing season and was 50 kg N ha-1 at maximum, while in August-September net immobilization was predominant with up to -100 kg N ha-1. Differences among crop species were not consistent across the site/years investigated. Sugar yield was lowest after rye at 3 site/years and correlated positively with Nmin in spring. Correlation between yield and cover crop N delivery was mostly low and inconsistent and could not be improved by a multiple regression approach. Thus, factors other than in-season N delivery from cover crops apparently impacted sugar beet yield formation to a larger extent.